Widespread osteoblastic metastases and marked elevation of CA19-9 as a presentation of signet ring cell gastric carcinoma - Link, Yuval; Romano, Asaf; Bejar, Jacob; Schiff, Elad; Dotan, Yaniv (Journal of Gastrointestinal Oncology; Vol 7, No 2 (April 01, 2016): Journal of Gastrointestinal Oncology, 2015)
Widespread osteoblastic metastases, as well as marked elevations of CA19-9 and carcinoembryonic antigen (CEA), are the initial manifestations of gastric signet ring cell carcinoma. CT Imaging revealed diffuse sclerotic metastases in the axial skeleton. It was only following gastric biopsy that the primary site of metastatic bone tumor was identified. Recent studies suggest that early diagnosis of cancer origin, including tumor molecular profiling, may dictate specific therapy, improve prognosis and increase patient survival rates.